Measles immunity gap among reproductive-age women participating in a simulated HIV vaccine efficacy trial in Zambia. Issue 5 (30th November 2022) - Malama, Kalonde; Tichacek, Amanda; Kelly, Hilary; Parker, Rachel; Inambao, Mubiana; Sharkey, Tyronza; Wall, Kristin M.; Kilembe, William; Price, Matt A.; Fast, Pat; Priddy, Fran; Allen, Susan
ABSTRACT: Measles is a vaccine-preventable viral disease whose vaccination coverage remains low in Zambia, where the target group for vaccination is children aged 9 to 18 months. In addition to inadequate measles vaccination coverage among children, few studies address potential resultant immunity gaps among adults. We analyzed data from a simulated HIV vaccine efficacy trial (SiVET) conducted from 2015–2017 among adult Zambian women of childbearing age to determine measles antibody seroprevalence before and after vaccination with the measles, mumps and rubella (MMR) vaccine. We used MMR vaccine as a substitute for an experimental HIV vaccine as part of a simulation exercise to prepare for an HIV vaccine efficacy trial. We found that 75% of women had measles antibodies prior to receiving MMR, which increased to 98% after vaccination. In contrast, mumps and rubella antibody prevalence was high before (93% and 97%, respectively) and after (99% and 100%, respectively) vaccination. The low baseline measles seropositivity suggests an immunity gap among women of childbearing age. We recommend that measles vaccination programs target women of childbearing age, who can pass antibodies on to neonates. Moreover, administering the MMR vaccine to clinical trial candidates could prevent measles, mumps or rubella-related adverse events during actual trials.